Hinterlands and regional dynamics in the ancient Southwest - Sullivan, Alan P.; Bayman, James (University of Arizona Press, 2007)
Hinterlands and Regional Dynamics in the Ancient Southwest is the first volume dedicated to understanding the nature of and changes in regional social autonomy, political hegemony, and organizational complexity across the entire prehistoric American Southwest. With geographic coverage extending from the Great Plains to the Colorado River, and from Mesa Verde to the international border, the volume's ten case studies synthesize research that enhances our understanding of the ancient Southwest's highly variable demographic, land use, and economic histories. For this volume, "hinterlands" are those areas whose archaeological records do not disclose the ceramic, architectural, and network evidence that initially led to the establishment of the Hohokam, Chaco, and Casas Grandes regional syst ...